(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
Agriculture and the industrial sector in industrialized nations continue to confront issues such as the need to increase food production and output, as well as the creation of employment possibilities for poor and rural people. Economic patterns as well as fast changes have an impact on the agricultural industry. The results revealed that there is a significant need for information technology to be utilized to solve issues, enhance production, and promote agriculture. However, information technology (IT’s interest in agriculture was not fully utilized. The adoption of modern information technology in the rural and agricultural sectors has been slower than in other economic sectors where it has been adopted at a faster pace. The purpose of this study is to look at the function, capability, and involvement of information technology in this industry, as well as to show how information technology may be used in various sectors of agriculture. Their findings were based on existing literature and economic theory, and they found that information technology has enormous potential in assisting farmers and stakeholders in improving agricultural performance, effectiveness, and profitability. Players, on the other hand, have additional disadvantages and challenges when it comes to the use and use of information technology. There are a variety of ways that information technology could be used to share data, including digital kiosks that not only provide essential resources such as telephone, schooling, health care, agriculture and irrigation, electronic banking, municipal services, and so on, as well as specialist networks that help define marketing options and optimum approaches. The use of information technology allows for accurate crop physiology forecasting in agriculture. The study of leaf protein is an intriguing subject that aids in the treatment of protein deficit and malnutrition. The present research focused on the role of information technology on agricultural productivity.